2006
DOI: 10.1590/s0102-311x2006001100005
|View full text |Cite
|
Sign up to set email alerts
|

Malnutrition in the second year of life and psychosocial care: a case-control study in an urban area of Southeast Brazil

Abstract: Malnutrition in the second year of life and psychosocial care: a case-control study in an urban area of Southeast Brazil Desnutrição no segundo ano de vida e cuidado psicossocial: estudo caso-controle em área urbana do Sudeste brasileiro (OR = 3.08;).

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
11
0
4

Year Published

2009
2009
2020
2020

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(18 citation statements)
references
References 15 publications
(13 reference statements)
0
11
0
4
Order By: Relevance
“…In Brazil, maternal social support has been associated with child nutritional status. 4,5 Other studies in Brazil have found informal social support to be negatively correlated with domestic violence 6 and positively related to coping with job stress. 7 Likewise, satisfaction with family relations has been associated with older women's quality of life.…”
mentioning
confidence: 96%
“…In Brazil, maternal social support has been associated with child nutritional status. 4,5 Other studies in Brazil have found informal social support to be negatively correlated with domestic violence 6 and positively related to coping with job stress. 7 Likewise, satisfaction with family relations has been associated with older women's quality of life.…”
mentioning
confidence: 96%
“…Infection causes malnutrition through reducing dietary intake and intestinal absorption, whereas malnutrition increases risk of diarrhea as it can predispose to infection due to weak immune system (Brown, 2003). Insu cient childcare doubles the probability of child malnutrition (Carvalhaes & Benicio, 2006).…”
Section: Introductionmentioning
confidence: 99%
“…A fase da alimentação complementar tem sido apontada como o período de maior vulnerabilidade nutricional da criança (1) , e a atuação sobre fatores psicossociais associados ao estado nutricional infantil, como um caminho para a obtenção de novos ganhos na redução da desnutrição (2)(3) . Há estudos indicando que comportamentos maternos e interações mãe/filho durante a alimentação podem ter papel importante na determinação do estado nutricional ou do consumo de alimentos pela criança (4)(5) .…”
Section: Introductionunclassified